THE CRIME OF AGGRESSION: COMPLEXITIES IN DEFINITION AND ELEMENTS OF CRIME - Mr. Maskun (Fakultas Hukum Universitas Gadjah Mada, 2013)
The infamous complexity of having a proper definition for crime of aggression began a long time ago. A working definition has been discussed by experts and scholars from time to time. However, they have not reached into a common understanding, including the International Law Commission. The amendment to the Rome Statute, taking place on June 12, 2010, was expected to deal with the problemsof definition. In addition it will also be a guidance to categorize such a crime as a crime of aggression,particular in terms of elaboration of elements of crime of aggression. Kompleksitas pendefinisian kejahatan agresi telah terjadi sejak beberapa tahun yang lalu. Definisi kejahatan agresi telah diperdebatkan oleh para ahli termasuk didalamnya Komisi Hukum Internasional, namun hingga kini perdebatan terus terjadi. Hasil amandemen atas Statuta Roma yang ber-langsung di Kampala Uganda 12 Juni 2010 akan menjadi jalan keluar untuk mengatasi perdebatan dimaksud. Di samping itu, amandemen tersebut dapat menjadi rambu-rambu dalam menguraikan elemen kejahatan agresi, sehingga kejahatan yang diduga sebagai kejahatan agresi dapat diuraikan dengan takaran yang baku (standard) menurut hukum internasional.